Взаємозв'язок особливостей будови та меж існування п'ятишарових сполук і фаз типу A5B5O17 - Тітов, Ю.О.; Слободяник, М.С.; Чумак, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The rated (a model of ideal layer perovskite-like structures) and experimental values of the periods of elementary cells of five-layer phases CaLn4–xLnIxTi5O17, SrLn4–xLnIxTi5O17, Ln5–xLnIxTi4FeO17 (Ln=La, Pr, Nd, LnI=Pr, Nd Sm, Gd, Dy, Yb) are analyzed. The interrelations between the peculiarities of a deformation of their crystal structure and the boundaries of morphotropic transitions of five-layer compounds and phases of the A5B5O17 type are established.